2022
DOI: 10.1038/s41598-022-05911-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of F-18 FDG PET/CT in fever or inflammation of unknown origin in a large single-center retrospective study

Abstract: Cause determination is challenging in fever or inflammation of unknown origin (FUO/IUO) despite today’s diagnostic modalities. We evaluated the value of F-18 FDG PET/CT in an unselected patient collective. This retrospective nonrandomized single-center study enrolled 300 male and female patients with FUO/IUO. PET/CT findings were compared with final clinical outcomes to determine the sensitivity, specificity, clinical significance, etiological distribution of final diagnoses, impact on treatment, role of white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…These results are also consistent with studies by Berrevoets et al and Vos et al which reported that use of 18 F-FDG PET/CT was associated with improved outcome in S aureus bacteremia [18,19]. 18 F-FDG PET/CT resulted in a change in management for about 30% of patients with fever of unknown cause (FUO/FUE) which is slightly lower than previously reported data in the literature where clinical utility for FUO has ranged from 33% to 54% [16,[20][21][22][23]. Heterogeneity in the definitions of 'clinical utility' may account for this wide range.…”
Section: Klebsiella Oxytoca + Lactobacillus Rhamnosussupporting
confidence: 91%
“…These results are also consistent with studies by Berrevoets et al and Vos et al which reported that use of 18 F-FDG PET/CT was associated with improved outcome in S aureus bacteremia [18,19]. 18 F-FDG PET/CT resulted in a change in management for about 30% of patients with fever of unknown cause (FUO/FUE) which is slightly lower than previously reported data in the literature where clinical utility for FUO has ranged from 33% to 54% [16,[20][21][22][23]. Heterogeneity in the definitions of 'clinical utility' may account for this wide range.…”
Section: Klebsiella Oxytoca + Lactobacillus Rhamnosussupporting
confidence: 91%
“…F-18 FDG PET/CT in patients followed up because of FUO/IUO was determined to have 88.1% sensitivity (95% CI: 74-96%), 37.5% specificity (95% CI: 15-64%), and 74.14% diagnostic accuracy (95% CI: 60-84%). The results of a newly published study showed a sensitivity of 80.2% and specificity of 89.8% for F-18 FDG PET/CT in contributing to the final diagnosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed reduced cerebral blood flow during CM using an FDG-PET in a murine model of experimental CM. FDG-PET was recently used systematically in a cohort of patients to help the diagnosis of fever of unknown origin [120], showing that this approach might become available to CM patients soon and may be able to complement the ongoing MRI studies to shed some light on the pathophysiological processes during the neurological syndrome.…”
Section: Investigative Neuro-imaging Toolsmentioning
confidence: 99%